1978
DOI: 10.1021/j100505a009
|View full text |Cite
|
Sign up to set email alerts
|

Resonance energy transfer between diphenylmethylene and fluorescein at 77 K

Abstract: Crampton for design and construction of the electrochemical cell and mounting apparatus, L. L. Steinmetz for discussions concerning the electronics, and B. W. Wallin for assistance with the lasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It is confirmed that the T 1 state of DPC is efficiently quenched by Rh6G or RhB. Wu and Trozzolo observed resonance energy transfer from DPC to fluorescein by means of fluorescence decay measurement and determined the value of R 0 to be 6.1 nm . We used Rh6G or RhB as the energy acceptor instead of fluorescein, because a considerable amount of emission from fluorescein mixes into the fluorescence of DPC.…”
Section: Resultsmentioning
confidence: 81%
“…It is confirmed that the T 1 state of DPC is efficiently quenched by Rh6G or RhB. Wu and Trozzolo observed resonance energy transfer from DPC to fluorescein by means of fluorescence decay measurement and determined the value of R 0 to be 6.1 nm . We used Rh6G or RhB as the energy acceptor instead of fluorescein, because a considerable amount of emission from fluorescein mixes into the fluorescence of DPC.…”
Section: Resultsmentioning
confidence: 81%